Avaliação da eficácia das áreas de proteção ambiental para a conservação dos elasmobrânquios do litoral amazônico - COELHO, Keyton Kylson Fonseca (2023)
Rays and sharks (Chondrichthyes, Elasmobranchii) are among the most endangered fish vertebrates on the planet. The pressure overfishing it has resulted in the reduction of population stocks across the planet. In this scenario, one of the main strategies used for the conservation of elasmobranchs is environmental protection areas (EPAs). This thesis aimed to evaluate the effectiveness of existing environmental protection areas on the coast of the state of Maranhão, Brazilian Amazon Coast, for the purpose of conservation of elasmobranch. First, we carried out a bibliographic review on research trends focusing on elasmobranchs from the Brazilian Amazon Coast the past four decades; thus highlighting the main areas studied, and species and the gaps in knowledge existing for elasmobranchs in the region. Then, through interviews guided by semi-structured questionnaires applied to artisanal fisher on the coast of the state of Maranhão, it was possible to develop a list of popular names of rays and sharks used by traditional communities, identifying the ethnotaxonomic standards applied in naming and classifying captured species by local artisanal fleets. In addition to the structure of the fishing fleet, we identified the most predatory fishing gear and the most vulnerable species of elasmobranchs in artisanal fisheries in the region. Using metrics in the biological, technological and conservation dimensions, we then evaluated whether the EPAs established on the coast of the state of Maranhão are effective for the conservation of elasmobranchs. We concluded that the studies carried out on elasmobranchs on our coast follow global research trends and that the local ecological knowledge of artisanal fisher can be an important tool for the management and sustainability of fishing, this traditional knowledge facilitates understanding bioecological aspects in the identification of species, highlighting which species are most vulnerable to the gear used, as well as reporting information that shows EPAs are ineffective for conservation of the elasmobranchs, proven by the constant capture of elasmobranchs in areas considered priority for conservation along the coast of Maranhão.